Treated Autoimmune Thyroid Disease Is Associated with a Decreased Quality of Life among Young Persons with Type 1 Diabetes - Spirkova, Alena; Dusatkova, Petra; Peckova, Monika; Kolouskova, Stanislava; Snajderova, Marta; Obermannova, Barbora; Stechova, Katerina; Hrachovinova, Tamara; Mares, Jiri; Cinek, Ondrej; Lebl, Jan; Sumnik, Zdenek; et al. (International journal of endocrinology, 2015)
Type 1 diabetes (T1D) in children and adolescents is relatively often accompanied by other immunopathological diseases, autoimmune thyroid disease (AITD) or celiac disease (CD). Our aim was to assess whether these conditions are associated with changes in the health-related quality of life (HRQOL) in pediatric patients with T1D. In a cross-sectional study we identified eligible 332 patients with T1D aged 8-18 years, of whom 248 (75%) together with their parents responded to the PedsQL Generic and Diabetes Modules. Compared to 143 patients without thyroid autoantibodies, 40 patients with a thyroxine-treated AITD scored lower in the overall generic HRQOL (P = 0.014), as well as in the overall diabetes-specific HRQOL (P = 0.013). After adjustment for age, gender, duration of diabetes, type of diabetes treatment, and diabetes control, this association remained statistically significant for the generic HRQOL (P = 0.023). Celiac disease was not associated with a change in the generic or diabetes-specific HRQOL (P = 0.07 and P = 0.63, resp.). Parental scores showed no association with AITD or celiac disease, except a marginally significant decrease in the overall generic HRQOL (P = 0.039) in the T1D + AITD compared to T1D group. Our study indicates that, in pediatric patients with T1D, concomitant thyroxine-treated AITD is associated with lower quality of life.